Attitudes towards mathematics and learning approaches in university students - Herrera Alvarez, Angela María; Cumpa Valencia, Moisés; Llanos Miranda, Kelva Nathali; Cerna Figueroa, Edwin Angel (Revista de Ciencias Sociales, 2024)
The study of attitudes toward mathematics has received much attention due to the influence it has on student learning and possibly the adoption of some approach. Therefore, the objective of this study was to analyze the association between attitudes towards mathematics and learning approach in a group of 228 university students of Pedagogy from a public university in Lima-Peru. The research has a quantitative approach and correlational design. Data collection was done using two instruments, the scale of attitudes towards mathematics and the revised Study Processes Questionnaire (R-CPE-2F). The results report that there is a direct association between the variables; it has also been found that learning approaches are associated to a greater extent with the dimensions of usefulness and motivation towards mathematics. Regarding the superficial approach, it has a positive association with the motivation and anxiety generated by mathematics, while the deep approach has a greater association with the usefulness, motivation, and confidence towards this subject. It is concluded, therefore, that the attitudes that students have towards mathematics would depend on several factors such as: Predisposition, motivation, and the usefulness they give it for their training.